Curcumin offsets PTZ-induced epilepsy: involving inhibition of apoptosis, wnt/β-catenin, and autophagy pathways. Issue 1 (1st January 2020) - Hamdy, Mona; Antar, Ashraf; El-Mesery, Mohamed; El-Shafey, Mohammed; Ali, Amr N.; Abbas, Khaled M.; Abulseoud, Osama Ali.; Hussein, Abdelaziz M.
ABSTRACT: Curcumin is a natural antioxidant isolated from Curcuma longa that proved to protect against experimentally induced epilepsy in animals. In the current work, we aimed to explore the possible molecular mechanisms of curcumin neuroprotective effect on PTZ-induced epilepsy in rats. Thirty male Sprague Dawley rats were subdivided into three groups: (a) normal control group, (b) PTZ group: rats received PTZ (50 mg/kg i.p. every other day) for 14 days, (c) curcumin + PTZ group: received PTZ as in PTZ group in addition to curcumin (200 mg/kg per oral daily) for 14 days. After each PTZ injection, the seizure stage, time to the first seizure and the duration of seizures were recorded. Also, at the end of experiment, oxidative stress markers, the expression of splitted caspase-3, β-catenin, LC3 (marker of autophagy), and alpha synuclein proteins were measured in brain tissues. treatment with curcumin caused significant reduction in seizure score, increased time to the first seizure and shortened seizure duration. Also, curcumin caused a significant reduction in oxidative stress (decreased MDA level and increased GSH level) and a significant reduction in the expression of splitted caspase-3, β-catenin, LC3 and alpha synuclein proteins. These results suggest that curcumin has a neuroprotective effect that is not attributed only to its antioxidant activity, but it involves also suppression of PTZ-induced apoptosis, Wnt/β-catenin and autophagy pathways.